2008
DOI: 10.1371/journal.ppat.1000154
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Telomere Directed Gene Expression during Initiation of Invasive Aspergillosis

Abstract: Aspergillus fumigatus is a common mould whose spores are a component of the normal airborne flora. Immune dysfunction permits developmental growth of inhaled spores in the human lung causing aspergillosis, a significant threat to human health in the form of allergic, and life-threatening invasive infections. The success of A. fumigatus as a pathogen is unique among close phylogenetic relatives and is poorly characterised at the molecular level. Recent genome sequencing of several Aspergillus species provides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
278
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(289 citation statements)
references
References 71 publications
9
278
2
Order By: Relevance
“…The flcB gene (but not flcA and flcC) is more expressed in vivo during initiation of murine infection 43 ; however, we have not observed increased flcA, -B and -C mRNA accumulation induced either by human platelets in vitro or during airway epithelial cells interacting with A. fumigatus conidia. 44,45 This represents the first evidence that a FLC homolog to be involved in virulence, since the impact of the C. albicans FLC null mutants on virulence was not evaluated.…”
Section: Discussioncontrasting
confidence: 87%
“…The flcB gene (but not flcA and flcC) is more expressed in vivo during initiation of murine infection 43 ; however, we have not observed increased flcA, -B and -C mRNA accumulation induced either by human platelets in vitro or during airway epithelial cells interacting with A. fumigatus conidia. 44,45 This represents the first evidence that a FLC homolog to be involved in virulence, since the impact of the C. albicans FLC null mutants on virulence was not evaluated.…”
Section: Discussioncontrasting
confidence: 87%
“…Other studies reported that transcriptional changes during the initiation of invasive aspergillosis involve more than 1,000 genes. However, in those studies, the authors compared fungal growth in vivo (during infection) vs. in vitro (on culture media) [21,22]. Therefore, the interpretation of these results and the subsequent conclusions have to be taken with caution, since transcriptomic studies depend on the experimental design, the time points studied and the type of reference sample used [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these findings, studies of the changes in gene expression during encounters with host tissues or in stress conditions have presented genes encoding proteins possibly involved in virulence [1720]. However, up to date, only a few experiments have been performed using organisms isolated from bronchoalveolar lavage from intranasal infection models [21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…As first speaker, Elaine Bignell, deputy director of the recently established Manchester Fungal Infection Group (MFIG), provided insights into the transcriptional response of A. fumigatus under host-imposed stress. 24,25 Moreover, she highlighted the presumed role of secreted factors for epithelial damage and introduced a mechanistic model on fungal persistence in the host lung environment. 26 The contribution of alveolar epithelial cells in fungicidal defense was demonstrated by in vitro studies as well as in murine infections, thereby affecting the immunotolerant disposal of inhaled A. fumigatus conidia.…”
Section: Feeding From the Host -Nutrition And Metabolism (Session 1)mentioning
confidence: 99%